Older Persons' Experiences of Depressive Ill-Health and Family Support - Anne Lyberg; Anne Lise Holm; Erna Lassenius; Ingela Berggren; Elisabeth Severinsson (Hindawi Limited, 2013)
The aim of this study was to explore experiences of the meaning of family support among older persons with depressive ill-health. Data were collected from twenty-nine participants through semistructured interviews and analysed using interpretative hermeneutic and reflective methodology. The findings revealed a main theme, hovering between feelings of belongingness and aloneness in relationships with family members, based on two themes: a sense of being worthy and a sense of being unworthy. Experiences of support and lack of support from family members were not opposites but connected in internal relationships and can be pictured as a movement on a continuum of ambiguity. Family support promotes the emotional needs of older persons with depressive ill-health to be confirmed. The family plays a vital role, not always by direct assistance, but indirectly by supporting the older person's own "guiding principles" for managing her/his situation. The feelings of aloneness as well as shame and guilt at poor or absent family responsiveness should be adequately addressed. Innovative nursing care can lead to improvement by focusing on acquiescence to the older person's life situation.